Effect of Different Solvent on The Antioxidant Capacity of Bidara Leaves Extract (Ziziphus Spina-Christi) - Rialdi, Azzahra Putri; Prangdimurti, Endang; Saraswati, Saraswati (Devotion : Journal of Research and Community Service, 2023)
Bidara leaves (Ziziphus spina-christi) contains secondary metabolites such as flavonoids, polyphenols, saponins, triterpenoids and tannins which can be a source of antioxidants. In Indonesia, bidara leaves are used as herbal medicine by boiling fresh leaves. The products that developed from bidara leaves are health supplements and herbal teas from bidara leaves, but scientific studies about the antioxidant compounds of bidara leaves are still limited. There are antioxidant components that are non-polar, semi-polar or polar. This study examines the polarity of antioxidant compounds in bidara leaves. In this study, bidara leaves dried with a fluidized bed dryer had better chemical and physical characteristics. The results of the extraction by using various solvents (water, ethanol, ethyl acetate, and hexane) with maceration method showed that the highest antioxidant capacity was in the ethanol fraction (p<0.05). These results were measured based on the antioxidant activity parameters that DPPH scavenging, FRAP values, total phenolic, and total flavonoids. These results indicate that most of antioxidant compounds in bidara leaves have high polarity.